Bamboo charcoal mediated plant secondary metabolites biosynthesis in tomato against South American tomato pinworm (Tuta absoluta) - Chen, Limin; Li, Xiaowei; Wang, Jinchao; Chen, Tingting; Zhang, Jinming; Zhu, Qianggen; Huang, Jun; Zhang, Zhijun; Hafeez, Muhammad; Zhou, Shuxing; Ren, Xiaoyun; Dong, Wanying; et al. (Frontiers in Sustainable Food Systems, 2023)
Recently, Tuta absoluta has been reported as an invasive insect pest species in China and has established itself in more than 33 prefectures, damaging mainly tomato crops. Immediate efforts have been initiated to find strategies to control this pest. It has been reported biochar could cause the improvement in plant growth and resistance to herbivory. In this study, we investigated the effects of different v/v ratios of biochar (bamboo charcoal) and coconut bran on the growth of tomato seedlings and the survival of T. absoluta. Our results indicated the most beneficial ratio of bamboo charcoal and coconut bran was 30:1. T. absoluta survival on bamboo charcoal grown tomato leaves (BC) reduced and the plant height, stem thickness, and chlorophyll content increased as compared to the control (CK). Metabolome profiling of BC and CK tomato leaves showed an increased accumulation of flavonoids, terpenoids, and phenolic acids in BC. Transcriptome sequencing resulted in the identification of 244 differentially expressed genes. Most of the upregulated genes were related to stress-related hub proteins, flavonoid biosynthesis, MAPK and phytohormone signaling, and terpenoid biosynthesis. Collectively, the transcriptome sequencing showed that genes associated with flavonoid and terpenoid biosynthesis were upregulated, whereas the expression of multiple genes related to signaling and defense was changed in response to bamboo charcoal supplementation. We conclude that bamboo charcoal induces bio-synthesis of flavonoids, terpenoids, and phenolic acids, which improve the plant growth and tolerance against T. absoluta, thus reducing the survival of destructive pest.